The Relationship Between Preceptor Role and Student Knowledge with Triage Skills in Emergency Department - Widiawati, Susi; Buhari, Basok; Sari, Rian Maylina; Febliandika, Valentino (KnE Life Sciences, 2021)
The Emergency Department is a place for clinical practice students to acquire triage experience. Triage can be carried out well by students who are supported by the supervisor and their own knowledge. The objectives of this study were to examine the relationship between the preceptor role and student knowledge with triage skills in emergency department. The research design was cross-sectional. The sample consisted of 43 nursing students who clinical practice in the emergency department. This study used accidental sampling technique. Data analysis used univariate and bivariate with the chi-square test. The results of the univariate analysis showed that 8.1% respondents had a good receptor role, 88.4% respondents had good knowledge and 60.5% nursing students had good of triage skills. The bivariate results showed a relationship between the role of supervisor and student knowledge with triage (p-value 0.006<0.05). Good triage implementation is supported by the supervisor and student knowledge. It is hoped that the hospital can apply the role of the preceptor to the maximum, set the preceptor schedule with the preceptee at the same time and the lecturers of educational institutions carry out simulations or equip students about triage optimal. Keywords: Preceptor, Knowledge, Triage Skills